Γ‐Crystallins of the chicken lens: remnants of an ancient vertebrate gene family in birds. (11th March 2016) - Chen, Yingwei; Sagar, Vatsala; Len, Hoay‐Shuen; Peterson, Katherine; Fan, Jianguo; Mishra, Sanghamitra; McMurtry, John; Wilmarth, Phillip A.; David, Larry L.; Wistow, Graeme
Abstract : γ‐Crystallins, abundant proteins of vertebrate lenses, were thought to be absent from birds. However, bird genomes contain well‐conserved genes for γS‐ and γN‐crystallins. Although expressed sequence tag analysis of chicken eye found no transcripts for these genes, RT‐PCR detected spliced transcripts for both genes in chicken lens, with lower levels in cornea and retina/retinal pigment epithelium. The level of mRNA for γS in chicken lens was relatively very low even though the chicken crygs gene promoter had lens‐preferred activity similar to that of mouse. Chicken γS was detected by a peptide antibody in lens, but not in other ocular tissues. Low levels of γS and γN proteins were detected in chicken lens by shotgun mass spectroscopy. Water‐soluble and water‐insoluble lens fractions were analyzed and 1934 proteins (< 1% false discovery rate) were detected, increasing the known chicken lens proteome 30‐fold. Although chicken γS is well conserved in protein sequence, it has one notable difference in leucine 16, replacing a surface glutamine conserved in other γ‐crystallins, possibly affecting solubility. However, L16 and engineered Q16 versions were both highly soluble and had indistinguishable circular dichroism, tryptophan fluorescence and heat stability (melting temperature T m 65 °C) profiles. L16 has been present in birds for over 100 million years and may have been adopted for a specific protein interaction in the bird lens. However, evolution has clearly reduced or eliminated expression of ancestral γ‐crystallins in bird lenses. The conservation of genes for γS‐ and γN‐crystallins suggests they may have been preserved for reasons unrelated to the bulk properties of the lens. Abstract : Two genes for lens γ‐crystallins are conserved in birds, although their expression is low compared with other vertebrates. The gene for γS maintains a lens‐preferred promoter. γS protein sequence is well conserved. However, all birds have one unusual residue change present for over 100 Myr. This has no effect on basic structure or stability; it likely evolved for a species‐specific protein interaction.